2007
DOI: 10.1063/1.2733649
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent spectroscopy of optical absorption enhancement in silicon photodiodes via scattering from surface plasmon polaritons in gold nanoparticles

Abstract: Experimental characterization and finite-element numerical simulations of the electromagnetic interaction between Au nanoparticles positioned atop a Si pn junction photodiode and incident electromagnetic plane waves have been performed as a function of wavelength. The presence of the Au nanoparticles is found to lead to increased electromagnetic field amplitude within the semiconductor, and consequently increased photocurrent response, over a broad range of wavelengths extending upward from the nanoparticle su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
221
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(234 citation statements)
references
References 12 publications
12
221
0
1
Order By: Relevance
“…13 The wavelength dependence of the absorption ratio shown in Fig. 5(b) is in qualitative agreement with the previous numerical researches, 14,15 in which d ∼ 5 nm is typically found in experiments. 16,17 Because an effective medium does not have near field or local field outside of the medium by definition, it is clear that the enhanced power absorption in the PV cell below the SP resonance when the gap d is increased (Fig.…”
Section: Mnps On Top Of a Pv Cellsupporting
confidence: 79%
“…13 The wavelength dependence of the absorption ratio shown in Fig. 5(b) is in qualitative agreement with the previous numerical researches, 14,15 in which d ∼ 5 nm is typically found in experiments. 16,17 Because an effective medium does not have near field or local field outside of the medium by definition, it is clear that the enhanced power absorption in the PV cell below the SP resonance when the gap d is increased (Fig.…”
Section: Mnps On Top Of a Pv Cellsupporting
confidence: 79%
“…6,7 In recent years there has been great interest in the possibility that electromagnetic excitations such as surface plasmons, localized or extended, might further facilitate light-trapping. [8][9][10][11] Zhou and Biswas reported calculations indicating enhancements beyond 4n 2 with a photonic crystal backreflector, 12 and recently Biswas and Xu reported that periodically patterned metal backreflectors also have enhancements beyond 4n 2 . 13 While photonic effects related to gratings, such as originally suggested by Sheng et al, 6 might explain these enhancements, a second possibility is that the sharing of electromagnetic energy between the surface plasmons and the waveguide modes of the thin film is involved.…”
Section: Introductionmentioning
confidence: 99%
“…1 Among noble metals, Au and Ag are two kinds of commonly used NP materials that exhibit strong localized surface plasmon resonances (LSPRs) from the ultraviolet to near-infrared bands, where the LSPR of these particles gives rise to strong optical scattering and near-field enhancement around the particle. In recent years, metal NPs have been investigated as a light trapping scheme to increase the optical absorption in optoelectronic devices [2][3][4][5][6][7] such as solar cells.…”
Section: Introductionmentioning
confidence: 99%